The RANKL expression and osteoclast in alveolar bone of rat diabetic model at different mechanical force application - Nuzulul Hikmah; Amandia Dewi Permana Shita; Hafiedz Maulana (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Diabetes is a serious and important public health problem, especially in relation to dental treatment. Because of its complications in periodontal tissue, diabetes can be contraindicated in patients undergoing orthodontic treatment. The receptor activator of nuclear factor-κb ligand (RANKL) is an essential cytokine inducing osteoclastogenesis. Osteoblasts produce this cytokine which has been suggested to play an integral role in osteoclast activation during bone remodeling of orthodontic tooth movement. Purpose: The aim of this study was to determine the correlation between RANKL expression of osteoblast and the number of osteoclasts in the alveolar bone of diabetic rat models at different mechanical force application. Methods: This study used animal subjects, white rats (Rattus norvegicus) of the Wistar strain (n=24) divided into six groups. The mechanical force to which they were subjected ranged between 10, 20, and 30 gramforce (grf). The animal models with diabetes were injected with a stratified dose of Streptozotocin. An orthodontic appliance was inserted in both the maxillary incisors for seven days. The tissue was subjected to histological analysis of osteoclasts and immunohistochemistry analysis of RANKL expression on the pressure and tension side of the alveolar bone. Results: The results of this study showed that the increase in mechanical force produced a rise in RANKL expression and osteoclast number on the pressure and tension side of the alveolar bone of diabetic rat models. Conclusion: There was a correlation between the RANKL of osteoblast and osteoclast numbers in the alveolar bone of diabetic models with different mechanical force application.